Prospective randomized control trial comparing metformin and clomiphine citrate as ovulation induction agent in women with polycystic ovarian syndrome at Alor Star Hospital, Malaysia. - Ridzuan, Jamaludin (2008)
To evaluate the effects of metformin on weight reduction , waist hip ratio , menstrual cycle and ovulation rates among women with polycystic ovarian syndrome with infertility taking metformin alone , clomiphene citrate alone and combination of metformin and clomiphene citrate. 115 patients diagnosed to have polycystic ovarian syndrome (according to the revised Rotterdam ESHRE/ASRM criteria, 2003) attending Infertility Clinic of Alar Star were recruited into the study and later randomized into three group i.e. Group A (metformin alone, n=38), Group 8 (CC alone, n=39) and Group C (combination of metformin and CC, n=38). During initial visit, the WHR were measured. Baseline investigations were taken which include follicular stimulating hormone, luteinising hormone, testosterone, liver function test, renal function test and serum prolactin. In Group A, metfromin 500mg tds were given up to 6 months. Clomiphene citrate 1 OOmg daily was given from the second until the sixth day of menstruation for those patients in Group B. The dosage was increased by 50mg for each cycle should anovulation was noted, to a maximur11 of 200mg. In Group C, a combination of metformin and clomiphene citrate were given and the dosage were similar to Group A and B. For all three groups, ovulation was confirmed by performing transvaginal scan. The WHR , serum follicular stimulating hormone , luteinising hormone and testosterone was repeated every three months. Metformin has no effects on weight reduction or waist hip ratio. 36.8% (14 out of 38 patients) and 57.9% (22 out of 38 patients) had spontaneous resumption of metformin , which might not due to the sole effect of metformin. Only 9 out of 38 patients (23.7%) taking metformin alone had ovulation compared to 28 out of 39 patients (71.8%) who take clomiphene citrate. This difference was significant statistically (p= 0.000). There was no difference in the number of patients having ovulation between those taking clomiphene citrate alone and combination of clomiphene citrate and metformin (28 out of 39 patients, 71 .8% and 26 out of 38 patients, 68.4% respectively; p= 0.470). Metformin has no effect on weight and waist hip ratio reduction. It should not be used to regulate menstrual cycle in PCOS patients. Its usage was no superior than the traditionally used clomphene citrate to bring ovulation among patients of polycystic ovarian syndrome with fertility problem . No additional advantage could be gained if it is combined with clomiphene citrate. Therefore, the current protocol to induce ovulation among polycystic ovarian syndrome with infertility patients with clomiphene citrate alone as the first line drug should remain.